The formation of innovation policy of the seaport - Оlga Afanasieva; Yana Pokora (Розвиток методів управління та господарювання на транспорті, 2020)
Nowadays the economic development of countries is determined not by natural resources and industrial production, but by the aggregate ability of economic entities to implement new ideas to meet consumer demand for certain goods or services. Seaports are key points of foreign trade. The quality and volume of exports of transport services, the level of competitiveness of national goods on the world market depend on the efficiency of seaports. There is a question of the necessity to develop an innovation policy that will stimulate economic activity, increase competitiveness, encourage the implementation of innovations, and resolve emerging contradictions.